CONTROLS ON THE EROSION OF CENOZOIC ASIA AND THE FLUX OF CLASTIC SEDIMENT TO THE OCEAN - Clift P.D. (My University, 2006)
Rates of continental erosion may be reconstructed from variations in the rate of accumulation of clastic sediment, most of which lies offshore. Global rates of marine sedimentation are usually considered to have reached a maximum after 3-4 Ma, driven by enhanced erosion in a variable glacial-interglacial climate. However, a new compilation of seismic data from the marginal seas of Asia now shows that only the Red River reached its historic peak after 4 Ma. Sediment flux from Asia first peaked in the early-middle Miocene (24-11 Ma), well before the initiation of a glacial climate, indicating that rock uplift and especially precipitation are the key controls on erosion, at least over long periods of geologic time. Reconstructions of weathering in East Asia show that faster erosion correlates with more humid, warm climates in the early-middle Miocene, changing to less erosive, drier climates after 14 Ma when Antarctic glaciation begins. Average rates of sedimentation on most east Asian continental margins since 1.8 Ma are 5-6 times less than the modern fluvial flux, implying that the flux to the oceans varies sharply on short timescales and is not always buffered over timescales of ~104 yr by storage in flood plains. © 2005 Elsevier B.V. All rights reserved.
Keywords: ASIA; CENOZOIC; CLIMATE; EROSION; MONSOON; Cenozoic